INSTRUMEN PEMBELAJARAN DAN PENINGKATAN SKILL DALAM MEMAKMURKAN MASJID SEBAGAI MEDIA DAKWAH - Zainul Arifin; Imam Baghowi; Ahmad Aqil Anwari; Isdianah Alda Rain; Anis Safitri; Mochamad Faisal Murad; Muhammad Fahmi Abdurrohman (STKIP Subang, 2026)
Mosques play a strategic role not only as places of worship, but also as centers of education, preaching, and community empowerment. The challenges of managing mosques in the modern era require improving the quality of human resources and implementing structured and sustainable learning instruments. This article aims to describe the implementation of community service through the application of learning instruments and skill enhancement in an effort to prosper the Al-Mujtahidin Mosque as a medium for Islamic preaching and education. The method used is Asset Based Community Development (ABCD) with a participatory approach involving ustadz, ustadzah, TPQ students, and mosque administrators in all stages of the activity. The results and discussion show that the application of systematic learning instruments can improve the quality of the TPQ learning process, strengthen educators' skills, and increase student enthusiasm and participation. In addition, a more structured, effective, and locally relevant learning pattern has been established. The conclusion of this activity indicates that strengthening community-based learning instruments significantly contributes to optimizing the mosque's function as an adaptive and sustainable center for education and da'wah.